Measuring precarious employment in times of crisis: the revised Employment Precariousness Scale (EPRES) in Spain - Alejandra Vives; Francisca González; Salvador Moncada; Clara Llorens; Joan Benach (Elsevier, 2015)
Objective: This study examines the psychometric properties of the revised Employment Precariousness Scale (EPRES-2010) in a context of economic crisis and growing unemployment. Methods: Data correspond to salaried workers with a contract (n = 4,750) from the second Psychosocial Work Environment Survey (Spain, 2010). Analyses included acceptability, scale score distributions, Cronbach's alpha coefficient and exploratory factor analysis. Results: Response rates were 80% or above, scores were widely distributed with reductions in floor effects for temporariness among permanent workers and for vulnerability. Cronbach's alpha coefficients were 0.70 or above; exploratory factor analysis confirmed the theoretical allocation of 21 out of 22 items. Conclusion: The revised version of the EPRES demonstrated good metric properties and improved sensitivity to worker vulnerability and employment instability among permanent workers. Furthermore, it was sensitive to increased levels of precariousness in some dimensions despite decreases in others, demonstrating responsiveness to the context of the economic crisis affecting the Spanish labour market.